2011
DOI: 10.1523/jneurosci.6311-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NMDA-Receptor Synaptic Transmission by Wnt Signaling

Abstract: Wnt ligands are secreted glycoproteins controlling gene expression and cytoskeleton reorganization involved in embryonic development of the nervous system. However, their role in later stages of brain development, particularly in the regulation of established synaptic connections is not known. We found that Wnt-5a acutely and specifically up-regulates synaptic NMDAR currents in rat hippocampal slices facilitating induction of LTP, a cellular model of learning and memory. This effect requires an increase in pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
155
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(162 citation statements)
references
References 33 publications
7
155
0
Order By: Relevance
“…We found that the time course of activation of PKC is faster than the activation of JNK, suggesting that these kinases could participate in the Wnt5a-induced potentiation of NMDARs via separate mechanisms. Different kinetics of activation induced by Wnt5a also explains why PKC is necessary for a rapid increase in NMDAR-mediated synaptic transmission, whereas JNK seems to potentiate NMDAR currents slowly and in a PKC-independent manner (17). A Wnt ligand considered to be a canonical ligand, Wnt7a, failed to activate PKC and JNK in dendrites but produced a slight increase in the activity of PKC and JNK in the soma of neurons in an RoR2-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that the time course of activation of PKC is faster than the activation of JNK, suggesting that these kinases could participate in the Wnt5a-induced potentiation of NMDARs via separate mechanisms. Different kinetics of activation induced by Wnt5a also explains why PKC is necessary for a rapid increase in NMDAR-mediated synaptic transmission, whereas JNK seems to potentiate NMDAR currents slowly and in a PKC-independent manner (17). A Wnt ligand considered to be a canonical ligand, Wnt7a, failed to activate PKC and JNK in dendrites but produced a slight increase in the activity of PKC and JNK in the soma of neurons in an RoR2-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…RoR2 signaling activates PKC and JNK, two kinases involved in the rapid up-regulation of NMDAR currents induced by Wnt5a (17). RoR2 signaling is also necessary to maintain basal level of NMDARmediated synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations